Dispersal pattern of coral larvae in Kuantan coastal waters, Malaysia - Hanapiah, Muhammad Faiz; Saad, Shahbudin; Ahmad, Zuhairi (Zibeline International Publishers, 2020)
Understanding source and sink pattern of coral larvae is among the key elements for effective ecosystem management and future habitat restoration. This study examined dispersal pattern of coral larvae among three known inshore reefs (Pulau Ular, Balok Reef and Raja Muda reef) in Kuantan coastal waters by simulating virtual larvae trajectories during spawning event in 2018. Dispersal pathways were mod elled and constructed by incorporating biological traits (timing of spawning and pelagic larvae duration) using Langragian particle tracking module integrated with 2-dimensional, hydrodynamic, flexible network model (MIKE 21 FM). Results indicated that Acroporid larvae moved in southward direction throughout dispersal period. Source and sink dynamic suggested that Pulau Ular has high larvae retention (70%) in which most of larvae originated from natal reef. Balok reef was dominant source of larvae for Raja Muda reef. Results also indicated that patches reefs near Raja Muda was ideal sink site for coral larvae and sh ould be prioritized for future ecosystem management action.